Development of the Basic Empathy Scale of Islamic Theology to Measure the Empathy of Islamic Education Teacher Candidates - Malyuna, Sita Isna; Suparto, Suparto; Kusaeri, Kusaeri; Hidayati, Zuhriyyah (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
The limited availability of empathy measurement instruments that align with Islamic values presents a significant challenge in the education of Islamic Religious Education teacher candidates in Indonesia. This study aims to develop and validate the Basic Empathy Scale - Islamic Theology, a modified version of the Basic Empathy Scale, designed to measure empathy based on Islamic values such as compassion, sincerity, tolerance, and mutual assistance. Employing a quantitative approach with an instrument development design, this research involved 211 respondents. The results of the Confirmatory Factor Analysis indicated a reasonably good model fit, with a Chi-Square (χ²) value of 384.623 (df = 132), p < 0.001, CFI = 0.829, TLI = 0.802, and RMSEA = 0.095, suggesting that the model is acceptable, though not perfect. The reliability coefficients-Cronbach's Alpha (α) = 0.809 and Omega (ω) = 0.816-demonstrate excellent internal consistency. The BES-IT was found to be a valid and reliable instrument for measuring empathy based on Islamic values. Its implication lies in supporting the development of the social-spiritual character of Islamic Religious Education teacher candidates and enhancing the contextual and responsive quality of religious education.